ZMIANY BATYMETRII JEZIORA MIERZYŃSKIEGO - Choiński, Adam; Ptak, Mariusz (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
The paper presents an analysis of changes in the bathymetry of Mierzyńskie lake, located in western Poland. It was found that over the last five decades this lake was characterized by exceptional stability in terms of changes in the surface area and volume of water, which decreased by 3.4 ha and 315,000 m3 respectively. The observed situation is quite different in comparison to the literature analysing the issue of lake evolution in Poland (indicating a faster rate of their disappearance). This specificity is due to the nature of the use of the catchment of this lake, which is characterised by an exceptionally high percentage of forest areas (considered to be the most natural) and negligible anthropopressure.